Pre‐eclampsia causing severe maternal morbidity – A national retrospective review of preventability and opportunities for improved care. (18th March 2019) - MacDonald, Evelyn Jane; Lepine, Sam; Pledger, Megan; Geller, Stacie E.; Lawton, Bev; Stone, Peter
Abstract : Introduction: Pre‐eclampsia and related sequelae are a leading cause of severe maternal and neonatal morbidity and mortality. A significant proportion of these poor outcomes may be preventable with improvements along the continuum of maternal and neonatal care. Aims: The aim of this study was to review cases of pre‐eclampsia resulting in severe maternal morbidity, describing the maternal and neonatal outcomes and the potential preventability of severe maternal morbidity (SMM). Materials and Methods: This was a retrospective cohort study of cases of SMM associated with severe pre‐eclampsia – a subset of a national SMM review study. Inclusion criteria for this subset were women who were pregnant or within 42 days of delivery with severe pre‐eclampsia as the main reason for admission to an intensive care unit or high dependency unit in New Zealand between 1 August 2013 and 31 January 2015 inclusive. A multidisciplinary expert panel reviewed cases for preventability using a validated preventability tool. Results: Of the 89 severe morbidities that were reviewed, 10 had eclampsia (11%) and there were four neonatal mortalities (4.3%). Multidisciplinary committees assessed the severe morbidity as potentially preventable in 31% (28) of cases with the majority due to delays in diagnosis and suboptimal treatment. Conclusion: We found a high level of preventable morbidity in cases of severe pre‐eclampsia with a concerning number of preventable eclampsia. Implementation of evidence‐based guidelines reinforced with education would assist clinicians to improve risk recognition, timely diagnosis and treatment and decrease potentially preventable severe morbidity associated with pre‐eclampsia.